Outcomes in Symptomatic Patients With Vertebrobasilar Dolichoectasia Following Endovascular Treatment - Wang, Jiejun; Jia, Luqiong; Yang, Xinjian; Jia, Xuecang; Liu, Jian; Liu, Peng; Miao, Zefeng; Zhang, Ying; Tian, Zhongbin; Wang, Kun; Wang, Zhongxiao; Zhang, Yisen; et al. (Frontiers in Neurology, 2019)
Objective: To evaluate whether the presenting symptoms of VBD predict outcomes following endovascular treatment. Methods: We retrospectively reviewed our institutional clinical database and identified 22 patients (all men; mean age: 52.6 years, range: 11–73 years) with a diagnosis of VBD, who underwent endovascular treatment from January 2010 to December 2017. Results: After analyzing the clinical and imaging data, we evaluated data for 22 symptomatic patients with VBD. At the time of VBD diagnosis, 13 patients (59%) had compressive symptoms, four (18%) had hemorrhagic symptoms, and five (23%) had ischemic symptoms. Nine of the 22 patients (41%), who presented with hemorrhagic and ischemic symptoms, achieved a satisfactory clinical and/or digital subtraction angiography imaging outcome after endovascular treatment. However, of the 13 patients who presented with compressive symptoms, seven (54%, 7/13) died from severe brainstem compression during follow-up; furthermore, magnetic resonance imaging showed worsening of the mass effect in eight patients with compressive symptoms (62%, 8/13). Conclusions: VBD is considered a challenging lesion without an ideal treatment modality. Endovascular treatment of VBD in patients presenting with compressive symptoms at diagnosis may not be beneficial. However, long-term outcomes following endovascular treatment may be acceptable in patients with non-compressive symptoms at diagnosis compared with those with compressive symptoms.